Note-taking roundhouse diagram strategy: improving student retention on body defense system concepts - Desi Trilipi; Bambang Subali; Yenny Anwar; Lucia Maria Santoso (Biosfer: Jurnal Pendidikan Biologi, 2019)
Note-taking Roundhouse diagrams strategy is a students' conceptual framework for interesting notes. This study aims to improve student retention on body defense system material through note-taking roundhouse diagram strategy. The method used was the one-group pretest-posttest design. The sample in this study was taken by simple random sampling technique. The number of samples in this study was 30 students. The instrument used in the study was a test instrument used multiple choice. This research was conducted during six meetings. Three meetings using roundhouse diagram with pretest and posttest. After four weeks, three more meetings were held to collect the second posttest (retest). The data were analyzed by t-test statistical analysis. Based on the results of the t-test statistical analysis at a significant level α = 0.05, it can be seen that t count > t table for short-term retention and long-term retention. The retention category also showed very satisfying results. Average results of N-gain score for short and long-term retention too very good. It can be included, the note-taking roundhouse diagram strategy on the body's defense system concept can improve student retention.